Longitudinal Viral Load Clustering for People With HIV Using Functional Principal Component Analysis - Yunqing Ma; Xueying Yang; Jiayang Xiao; Xiaoming Li; Bankole Olatosi; Jiajia Zhang (AIDS Research and Treatment)
Discussion: The findings highlight the impact of continuous clustering in understanding the distinct viral profiles of PWH and emphasize the importance of tailored treatment and insights to target interventions for all PWH.